Investigation into feed preparation for regulatory fish metabolism studies1. (26th July 2013) - Goeritz, Ina; Atorf, Cornelia; Whalley, Paul; Seymour, Paul; Klein, Michael; Schlechtriem, Christian
Abstract BACKGROUND Test diets used in fish metabolism studies for regulatory purposes must be homogenously fortified with the radiolabelled test substance and stable with respect to leaching. Standard fish food, as used in commercial fish farming, should also be used in fish metabolism studies. Therefore, suitable spiking and coating procedures are required to ensure the correct dosing of the fish during the experiment. RESULTS Methods for the homogeneous, safe and efficient application of radiolabelled test items to the surface of commercial feeding pellets were developed. Leaching studies showed that test items of low lipophilicity applied to feeding pellets need to be stabilised, to reduce the risk of significant losses prior to ingestion by the fish. Coating of solvent‐spiked pellets with calcium alginate was shown to reduce leaching losses of water‐soluble test items significantly. Alternatively, commercial feeding pellets can be coated with alginate or vegetable oil fortified with a radiolabelled test item also leading to sufficiently stabilised test diets. Experimental conditions, such as the water temperature, may have a significant effect on the leaching behaviour of the test items. CONCLUSIONS A detailed description of different spiking and coating procedures for the preparation of experimental diets suitable for fish metabolism studies is provided. © 2013 Society of Chemical Industry